2015
DOI: 10.1007/s11010-015-2454-7
|View full text |Cite
|
Sign up to set email alerts
|

AP4 activates cell migration and EMT mediated by p53 in MDA-MB-231 breast carcinoma cells

Abstract: Tumor metastasis is the primary cause of mortality in most cancer patients. Before disassociation from the tumors, most of malignant tumor cells undergo the epithelial-mesenchymal transition to break away from the adhesions between the cells and the surrounding extracellular matrix. Recently, activating enhancer-binding protein (AP4) has been shown to be a mediator of EMT in colorectal cancer and high level of AP4 correlates with poor prognosis in cancer patients. It has been found that AP4 upregulates the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
(58 reference statements)
2
12
0
Order By: Relevance
“…Similar to our results, AP4 has been reported to promote cell growth in HCC [41], colorectal carcinoma [42] and gastric cancer [43]. Moreover, it has been proposed that AP4 could activate cell migration and EMT mediated by p53 in MDA-MB-231 cells [44] and mediate a c-MYC-induced EMT in colorectal cancer [45].…”
supporting
confidence: 90%
“…Similar to our results, AP4 has been reported to promote cell growth in HCC [41], colorectal carcinoma [42] and gastric cancer [43]. Moreover, it has been proposed that AP4 could activate cell migration and EMT mediated by p53 in MDA-MB-231 cells [44] and mediate a c-MYC-induced EMT in colorectal cancer [45].…”
supporting
confidence: 90%
“…Interestingly, several genes that were downregulated such as ST3GAL 6 ( 55 ), FOXM1 ( 56 ) and AP4 ( 57 ) play a key role in breast cancer tumorigenesis and this interested us to probe more carefully how this regulation was orchestrated by the PRMT5/ WDR77 complex.…”
Section: Resultsmentioning
confidence: 99%
“…Recently they showed that AP4 stimulates the epithelial-mesenchymal transition in colorectal cancer [19], and AP4 suppresses cellular senescence by directly repressing p16 and p21 expression in AP4-deficient mouse embryo fibroblasts (MEFs) [20]. Our study previously demonstrated that AP4 can regulate cell migration via the activity of p53 in breast cancer cells [21]. We also shown that transcription factor AP4 in Drosophila controls tracheal terminal branching and cell growth [22].…”
Section: Introductionmentioning
confidence: 66%
“…Besides, several studies have shown that AP4 is expressed at elevated levels in several types of cancer, including pancreatic cancer [23], colorectal cancer [14], and gastric cancer [24]. High expression of AP4 correlated with poor patient survival and metastasis in cancers [21,24]. However, the cellular functions of high AP4 level in noncancerous cells are rarely reported.…”
Section: Introductionmentioning
confidence: 99%